HUBUNGAN TUGAS KELUARGA DENGAN KEPATUHAN DIET DIABETES MILITUS TIPE 2 PADA LANSIA - Wulansari, Wiranti Dwi; Yunan Y, Endang Yuswatiningsih (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2019)
There is no family duties, Diabetes Mellitus patients will not obey implement diet, so uncontrolled Diabetes Mellitus and complications occur. The research objective to analyzes of family duties improve patient compliance of Diabetes Mellitus diet compliance of diabetes militus type 2 on elderly. This research was cross sectional with the population were elderly who had diabetes militus in the village grabahan sub-district of karangrejo Magetan regency. The samples were 31 people with technique of simple random sampling. Date colleting used questionnaire. Date processing technique used editing, coding, scoring, tabulating and Date analyzing used test of rankspearman. The research result showed proven there was relation of family duties with diet compliance diabetes militus type 2 in the village of Grabahan sub-district of Karangrejo Magetan regency. Based on the test of spearman was obtained (p=0,017) < ? 0,05, so H1 was accepted. it was obtained from 31 respondents there were a large proportion of respondents 17 had good family duties (54,8%) and as many as 21 respondents had obedient compliance (67,7%). The conclusion of this research was that there’s relation of family duties with diet compliance diabetes militus type 2 on elderly in the village of Grabahan su-district Karangrejo Magetan regency. Keywords: diet diabetes militus , family duties, compliance